PENGEMBANGAN GAME EDUKASI MATEMATIKA BERBASIS ANDROID MENGGUNAKAN SOFWARE CONSTRUCT 2 TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS - Rosa Yuliana; Muhamad Firdaus; Dwi Oktaviana (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2022)
The research method used in this research is Research and Development. The subjects in this study consisted of validation subjects consisting of material and media validators and test subjects consisting of 23 grade VII junior high school students. The research was conducted at SMP Negeri 10 Sungai Kakap. The instruments used in the study consisted of expert validation sheets, respondent questionnaires, and tests of mathematical understanding abilities. The purpose of this study was to determine the process of developing an Android-based math educational game using software construct 2 on mathematical abilities. The results of the study are as follows: The level of feasibility of an Android-based math education game using software construct 2 on the ability to understand the results obtained is 88.66% with very feasible criteria. The level of attractiveness of an Android-based math education game using software construct 2 on the ability to understand the results obtained is 88.19% with very interesting criteria. Improved mathematical understanding skills after the application of Android-based math education games. There is an increase From the calculation results obtained tcount> ttable = 8.85987> 1.71714, thus Ho is rejected Ha accepted.